IMPLEMENTASI BIMBINGAN SELF CONFIDENCE UNTUK MENINGKATKAN SELF LEADERSHIP SISWA SEKOLAH DASAR - Handayani, Pristy Wikan; Asrowi, Asrowi; Wiyanti, Sri (Universitas Sebelas Maret, 2016)
This research was Research and Development which produced a teachers? guides that is worthy and effective as the development of guidance material on self confidence to enhance the self leadership of fifth grade student of elementary school. Results of the analysis expert-practitioners examination showed that the guidance material were proved in good categories. The results of these examination are supported by a small group of examination results which indicated a high acceptability. Results of examination trial product on limited subject showed that the hypothesis was proven. The conclusions of this study is the implementation of the guidance about self confidence is deveserves and effective to enhance self leadership of the elementary school student.